Coordination of single-phase rooftop PVs to regulate voltage profiles of unbalanced residential feeders - Safitri, N.; Masoum, Mohammad Sherkat; Shahnia, Farhad (IEEE, 2014)
Installation of single-phase rooftop Photovoltaic (PV) systems in low voltage distribution networks is gaining increasing popularity in many countries including Australia. Utilization of rooftop PVs in residential feeders without controlling their ratings and locations may deteriorate the overall grid performance including power flows, losses and voltage profiles. This paper investigates the effectiveness and limitations of two different methods for regulating the voltage profile at low voltage residential feeders with single-phase rooftop PVs. These methods are based on the availability of voltmeters at each phase at each bus along the low voltage feeder which transmit their measurements to the controllers of the PV inverters. The main objective is to regulate the voltage profiles and reduce the voltage unbalance using drool control. The algorithm considers reactive power exchange and active power curtailment of the single-phase rooftop PVs. MATLAB-based simulation results demonstrate effectiveness of the proposed approach.